Ferroptosis in central nervous system injuries: molecular mechanisms, diagnostic approaches, and therapeutic strategies - Huang, Qiuhu; Zhang, Haowen; Chen, Shenbo; Wang, Yao; Zhou, Jian (Frontiers in Cellular Neuroscience, 2025)
Ferroptosis, an iron-dependent form of cell death, has emerged as a critical factor in the pathogenesis of central nervous system (CNS) injuries, including neurodegenerative diseases, stroke, and traumatic brain injury. This review highlights disrupted iron metabolism, glutathione depletion, and antioxidant system impairment as core mechanisms, alongside polyunsaturated fatty acid oxidation contributing to neuronal damage. Diagnostic advancements, such as MRI-based iron quantification and lipid ROS detection, offer clinical potential but require validation. Therapeutic strategies, including iron chelators, antioxidants, and lipid metabolism modulators, demonstrate efficacy in preclinical models by attenuating ferroptosis. Translational challenges persist due to incomplete mechanistic insights, tissue-specific iron dynamics, and delivery limitations. The dual role of iron in CNS physiology and pathology underscores the need for interdisciplinary research to refine diagnostics and therapies. Emphasizing ferroptosis as a therapeutic target, this work advocates for a deeper exploration of immune interactions and combinatorial approaches to improve outcomes in CNS injuries.